Influences of Different Drop Height Training on Lower Extremity Kinematics and Stiffness during Repetitive Drop Jump - I-Lin Wang; Yi-Ming Chen; Ke-Ke Zhang; Yu-Ge Li; Yu Su; Chou Wu; Chun-Sheng Ho (Applied Bionics and Biomechanics)
Drop jump (DJ) is often used as a plyometric exercise to improve jumping performance. Training from improper drop heights and for improper durations lead to unfavorable biomechanical changes in the lower extremities when landing, which result in reduced training effects and even lower extremity injuries. Purpose. To study the effects of repeated DJ training at drop heights of 30 cm, 40 cm, and 50 cm (drop jump height (DJH) 30, DJH40, and DJH50) on lower extremity kinematics and kinetics. The 1st, 50th, 100th, 150th, and 200th DJs (DJ1, DJs50, DJs100, DJs150, and DJs200) were recorded by using a BTS motion capture system and force platform. The MATLAB software was used to compare the kinematic and stiffness data of DJ1, DJs50, DJs100, DJs150, and DJs200 with one-way ANOVA repeated measure. If there were significant differences, the LSD method was used for post hoc comparisons. Methods. Twenty healthy male Division III athlete volunteers were selected as subjects, and 200 drop jumps (DJs200) were performed from DJH30, DJH40, and DJH50. Results. The jumping height (JH), contact time (CT), and GRF increased with drop height, and the stiffness of the legs and ankle at DJH30 was higher than that at DJH40 and DJH50 (p<0.05). Conclusion. Within DJs200, training at DJH50 yield the high impact easily leads to lower extremity injury; training at DJH30 can increase the stiffnesses of the legs and ankle joints, thus effectively utilizing the SSC benefits to store and release elastic energy, reducing the risk of lower extremity musculoskeletal injury. Therefore, coaches can choose different drop heights and training quantities for each person to better prevent lower extremity injury.